The interaction of RNA G-quadruplexes from the influenza A virus vRNA with TMPyP4 and BRACO-19 ligands - Maria Nalewaj; Joanna Sliwiak; Karolina Zielinska; Pawel Zmora; Dorota Niedziałek; Grzegorz Wieczorek; Elzbieta Kierzek; Marta Szabat (PLoS ONE, 2025)
The influenza virus is an interesting research subject due to its serious threat to global public health. To date, various structural motifs from the influenza A virus (IAV) genome have been studied. Recently, RNA G-quadruplexes (G4s), noncanonical structures formed within the G-rich sequences of the IAV genome, have been reported. These motifs are suggested to be promising antiviral targets, and studying the G4 binding ligands has attracted increasing research interest. We hypothesized that RNA G4s can play a crucial role in IAV replication. This study focused on the interactions between RNA G4s and ligands, which have not been extensively studied in the influenza A virus California/4/2009 (H1N1) to date. Herein, commonly used G4-specific ligands, TMPyP4 and BRACO-19, were selected. First, we performed a reverse transcription stop assay to study the effect of both ligands on the inhibition of cDNA synthesis. Our results showed that both compounds inhibited this process in all wild-type G4 variants, with one variant exhibiting the most noticeable effect after the addition of TMPyP4. We also examined the binding affinity of TMPyP4 and BRACO-19 to IAV RNA G4s using isothermal titration calorimetry, circular dichroism, and fluorescence spectroscopy. Some differences in the binding properties of the three selected G4s were found. Furthermore, UV melting analysis was conducted to evaluate the effect of the ligands on the thermal stability of RNA G4s. To supplement our experimental approaches, we applied, in the limited range, molecular modeling to simulate the folding of 1Q G-quadruplex and provide further insights into its structural stability and topology. Finally, the influence of TMPyP4 on the IAV minireplicon activity was investigated, revealing significant inhibition of IAV replication. Overall, interactions between TMPyP4 and BRACO-19 with IAV G4s were demonstrated for the first time, suggesting that G4s can be potential anti-influenza drug targets.